Media Pembelajaran Berbasis Teknologi Informasi Di Taman Kanak-Kanak - Herman Herman; Rusmayadi Rusmayadi; Herlina Herlina; Herman (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. Partners of this Community Partnership Program are IGTKI South Sulawesi Province. The problems are: (1) The teacher's lack of understanding of the usefulness of information technology in making learning media; (2) the minimal use of information technology in the learning process; (3) The teacher's need for a training to make learning media based on information technology intensively. The external target is learning media based on information and communication technology and is interesting and in accordance with the characteristics of early childhood. The methods used are: lectures, demonstrations, discussions, questions and answers, and companion partners. The results achieved are (1) partners have knowledge and understanding of the usefulness of information technology in making learning media (2) partners have the skills to design and design learning media that are attractive and in accordance with the characteristics of early childhood, (3) partners have the ability to improve educational quality of learning